Metalização mecânica com Ti de placas de Al2O3 utilizando máquina ferramenta computadorizada para brasagem metal/cerâmica - Vieira, Joâo Dantas Paiva (2015)
In this work employed the mechanical metallization technique to produce a thin film of titanium in the ceramic substrate of alumina (Al2O3), in order to favor wetting with conventional adding alloys. Was used an automated process with employment a machine tool computer numerical control (CNC) without operator intervention. Subsequently, the metallized ceramic was brazed with metallic stainless steel tube 304, by indirect technique in high-vacuum oven, using conventional alloying addition Ag- 28Cu. The resulting interface was characterized by technique of micro structural analysis using scanning electron microscopy (SEM) coupled with energy dispersive spectroscopy (EDS) for chemical microanalysis and mechanical performance, shear test, carried out on a universal testing machine. The titanium metallization film was observed by electron microscopy showing an interface with good interaction between the elements of the materials involved, and the thickness of the layer of titanium fairly regular, consistent with results in the same work area. While brazing interface presented some defects, mainly due to the furnace atmosphere and vacuum pressure, which has not reached the specified value, identified in other studies, which influenced, to some extent, the mechanical results.